Analysis of Tall Structure Considering Soft Storey Under Dynamic Loading using ETABS - Sakshi Sahu; Pradeep Kumar Nirmal; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2022)
There has been a steady rise in urbanisation in the last few years which has led to major issues in parking vehicles and made the street busy. Such cases have led engineers to plan parking spaces even on the first floor for the purpose of parking. Structures with RC frames with the open ground floor without infill are subjected to heavy lateral loads and prove to fail in case of heavy earthquake loads. When masonry infill interacts with its surrounding frames, the lateral stiffness and lateral load-carrying capacity of the structure significantly increase. The presence of masonry infill walls affects how the structure behaves overall when subjected to lateral forces. Earthquakes that occurred recently have shown that a large number of existing reinforced concrete buildings especially soft storey building are vulnerable to damage or even collapse during a strong earthquake. The building’s first floor exhibited soft behaviour, and the earthquake prevented the columns from offering enough shear strength. This research is carried out with various building models such as soft storey structure with and without steel bracings. In the second case the steel bracing is provided at the center of the structure. The study uses ETABS software to analyse a soft storey structure using the pushover analysis method, and it must provide the results and analysis’s conclusion.